Sporadic adenomatous polyp regression with exisulind is effective but toxic: a randomised, double blind, placebo controlled, dose-response study. Issue 3 (8th September 2005) - Arber, N; Kuwada, S; Leshno, M; Sjodahl, R; Hultcrantz, R; Rex, D
Abstract : Background and aim: A 12 month, multicentre, randomised, double blind, placebo controlled, phase 3, dose-response study was carried out. Exisulind inhibits tumour growth by induction of apoptosis. The aim of our study was to investigate if exisulind induces regression of sporadic colonic adenomas. Patients and methods: A 12 month multicentre randomised double blind placebo controlled phase 3 dose response study was carried out. At baseline colonoscopy, left sided polyps (3–10 mm) were tattooed, measured, and left in place. Subjects received exisulind 200 or 400 mg, or placebo daily. Follow up sigmoidoscopy was performed after six months, and removal of any remaining polyps at the 12 month colonoscopy. The primary efficacy variable was change in polyp size from baseline. Results: A total of 281 patients were enrolled and randomised; 155 (55%) fulfilled the criteria for the intention to treat (ITT) analysis and 114 (41%) fulfilled the criteria for the efficacy evaluation analysis (patients who underwent the 12 month colonoscopy). The decrease in median polyp size was significantly greater (p = 0.03) in patients who received exisulind 400 mg (−10 mm 2 ) compared with those who received placebo (−4 mm 2 ). Complete or partial response was significantly higher in the exisulind 400 mg group (54.6%) compared with the placebo group (30.2%), and disease progression was significantly lower (6.1% v 27.9%) (p = 0.04 and 0.02, respectively). Increased liver enzymes (8.4%) and abdominal pain (14.7%) were also reported at a greater frequency in the exisulind 400 mg group. Conclusion: Exisulind caused significant regression of sporadic adenomatous polyps but was associated with more toxicity. This model of polyp regression, short in its term and involving a comparatively small patient sample size, may be the best available tool to assess a therapeutic regimen before launching into large preventive clinical studies.